Richard Varick papers - Varick, Richard, 1753-1831.
Letters (1780, 1811, 1813) written by Varick to Jane Varick Hardenburgh DeWitt, K. K. Van Rensselaer, and Abraham Van Vechten; newspaper article (1849) on George Washington's religious beliefs documented by letters from Varick and Edmund D. Barry; biographical sketch; and photographs of portraits of Varick and his wife, Maria Roosevelt Varick.
In part, typewritten transcripts.
Army officer, New York State attorney general, and mayor of New York, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Barry, Edmund D. -- Correspondence; DeWitt, Jane Varick Hardenburgh -- Correspondence; Van Rensselaer, K. K. -- 1763-1845 -- Correspondence; Van Vechten, Abraham, -- 1762-1837 -- Correspondence; Varick, Maria Roosevelt, -- 1763-1841.; Washington, George, -- 1732-1799 -- Religion; New York (N.Y.) -- Politics and government -- To 1898.; New York (State) -- Politics and government -- 1775-1865.; New York (State) -- History -- 1775-1865.; United States -- History -- 1783-1865.; Army officers; Mayors -- New York (State) -- New York; Public officials -- New York (State)